The effectiveness of mangosteen rind extract as additional therapy on chronic periodontitis (Clinical trials) - Hendiani, Ina; Hadidjah, Dede; Susanto, Agus; Setia Pribadi, Indra Mustika (Padjadjaran Journal of Dentistry, 2017)
Introduction: Periodontitis is an inflammatory disease that attacks the periodontal tissue comprises the gingiva, periodontal ligament, cementum and alveolar bone caused mainly by plaque bacteriophage or other specific dominant type of bacteria. The purpose of this study was to determine the therapeutic effect of clinical application of mangosteen peel extract gel as adjunctive therapy scaling and root planing in patients with chronic periodontitis. This research was expected to developed new treatment in the field of dentistry, particularly in periodontics, which can be used as supporting material for the treatment of chronic periodontitis. Methods: Quasi-experimental research, split mouth, with as many as 14 chronic periodontitis patients. Mangosteen rind was prepared to be formed into extract gel, dried at room temperature, then the dried samples were macerated by using ethanol, then evaporated and decanted for 3 days until obtained condensed extract. The samples were patients with chronic periodontitis in at least 2 teeth with pockets â¥ 5 mm. Clinical parameters of pocket depth, gingival bleeding, and clinical epithelial attachment level were measured at baseline and 1 month after treatment. Analysis of data using the t-test. Results: The comparison of average gap ratio of pockets depth, gingival index, gingival bleeding and epithelium attachment levels, before and after treatment showed significant differences, such as in the test and control sides. Conclusion: The mangosteen rind gel as adjunctive therapy for scaling and root planing is able to reduce pockets depth, gingival index, and gingival bleeding, and improve clinical epithelial attachment.